Efficacy and safety of first-line avelumab in patients with advanced non-small cell lung cancer: results from a phase Ib cohort of the JAVELIN Solid Tumor study - James L Gulley; Jaafar Bennouna; Guy Jerusalem; Janice Mehnert; Matthew Taylor; Karen Kelly; David Spigel; Marcis Bajars; Claire F Verschraegen; Edward F McClay; Nicholas Iannotti; Charles H Redfern; et al. (Journal for ImmunoTherapy of Cancer)
Introduction Avelumab, an antiprogrammed death ligand-1 antibody, is approved as a monotherapy for treatment of metastatic Merkel cell carcinoma and advanced urothelial carcinoma, and in combination with axitinib for advanced renal cell carcinoma. We report the efficacy and safety of first-line avelumab in advanced non-small cell lung cancer (NSCLC).Methods In a phase I expansion cohort of the JAVELIN Solid Tumor trial, patients with treatment-naive, metastatic, or recurrent NSCLC received 10 mg/kg avelumab intravenously every 2 weeks. Endpoints included best overall response, duration of response (DOR), progression-free survival (PFS), overall survival (OS), and safety.Results Overall, 156 patients were enrolled and treated. Median duration of follow-up was 18.6 months (range, 15 to 23 months). The objective response rate was 19.9% (95% CI, 13.9 to 27.0), including complete response in 3 (1.9%) and partial response in 28 (17.9%). Median DOR was 12.0 months (95% CI, 6.9 to not estimable). Median PFS was 4.0 months (95% CI, 2.7 to 5.4) and the 6-month PFS rate was 38.5% (95% CI, 30.7 to 46.3). Median OS was 14.1 months (95% CI, 11.3 to 16.9) and the 12-month OS rate was 56.6% (95% CI, 48.2 to 64.1). Treatment-related adverse events (TRAEs) occurred in 107 patients (68.6%), including grade ≥3 TRAEs in 19 (12.2%). Immune-related adverse events and infusion-related reactions occurred in 31 (19.9%) and 40 patients (25.6%), respectively. No treatment-related deaths occurred.Conclusion Avelumab showed antitumor activity with a tolerable safety profile as a first-line treatment in patients with advanced NSCLC. These data support further investigation of avelumab in the phase III JAVELIN Lung 100 study.Trial registration details ClinicalTrials.gov NCT01772004; registered January 21, 2013.